Medical Home Transformation in Pediatric Primary Care—What Drives Change? - McAllister, Jeanne W. (American Academy of Family Physicians, 2013)
PURPOSE: The aim of this study was to characterize essential factors to the medical home transformation of high-performing pediatric primary care practices 6 to 7 years after their participation in a national medical home learning collaborative. METHODS: We evaluated the 12 primary care practice teams having the highest Medical Home Index (MHI) scores after participation in a national medical home learning collaborative with current MHI scores, a clinician staff questionnaire (assessing adaptive reserve), and semistructured interviews. We reviewed factors that emerged from interviews and analyzed domains and subdomains for their agreement with MHI and adaptive reserve domains and subthemes using a process of triangulation. RESULTS: At 6 to 7 years after learning collaborative participation, 4 essential medical home attributes emerged as drivers of transformation: (1) a culture of quality improvement, (2) family-centered care with parents as improvement partners, (3) team-based care, and (4) care coordination. These high-performing practices developed comprehensive, family-centered, planned care processes including flexible access options, population approaches, and shared care plans. Eleven practices evolved to employ care coordinators. Family satisfaction appeared to stem from better access, care, and safety, and having a strong relationship with their health care team. Physician and staff satisfaction was high even while leadership activities strained personal time. CONCLUSIONS: Participation in a medical home learning collaborative stimulated, but did not complete, medical home changes in 12 pediatric practices. Medical home transformation required continuous development, ongoing quality improvement, family partnership skills, an attitude of teamwork, and strong care coordination functions.